EFFECT OF COMPUTER SUPPORT IN MATHEMATICS ACHIEVEMENT OF TECHNICAL UNIVERSITY STUDENTS - Elena P. Bogomolova; Olga V. Maksimova (Открытое образование (Москва))
This paper studies the influence of information technology on the process of teaching mathematics at the Technical University. We consider the didactic aspects of computer use in practical classes in higher mathematics. We analyze a combination of traditional and computer control on mathematical disciplines within the competence model of bachelor of engineering areas.